Feasibility of Indirect immunofluorescence (IIF) alone as a screening method for antinuclear antibody in connective diseases in India's sub-Himalayan region - Deepjyoti Kalita; U Sashi Rekha; Anusha K Raj; Putul Mahanta; Pratima Gupta; Sangeeta Deka (Wolters Kluwer Medknow Publications, 2022)
Background: For the management of connective tissue disorders (CTDs), antinuclear antibody (ANA) testing is essential, both from diagnostic and prognostic points of view. Usually, patterns obtained by ANA-IIF testing correlates to specific autoantibodies as obtained from the test for ENA (by LIA/ELISA, etc.). But to apply these data from western studies, we may need validation in the local population like our subjects in sub-Himalayan (Garhwal region) area where CTDs are common. Also, suppose ANA-IFA pattern's correlation is reliably known in our population, it can minimize the cost of managing CTDs by limiting ENA testing, which is 10 times costlier than ANA-IIF. Hence, this study was undertaken to know the specific autoantibody targets (ENA by LIA) against ANA-IIF patterns in our local population. Materials and Methods: In this retrospective cross-sectional work, serum samples of CTDs were tested for ANA by IIF (Euroimmune AG) and ENA by LIA (Euroline ANA-3G) continuously for 36 months. The manufacturer's kit insert was followed, and results were analyzed applying appropriate statistical methods. Results: Major ANA-IIF patterns were found to be associated with specific autoantibodies, for example, Nuclear homogenous with dsDNA, nucleosomes, histones; speckled pattern with nRNP/Sm, Sm, SSA/Ro-52, SSB; nucleolar pattern with Scl-70, Pm-Scl 100 and centromere pattern with CENP-B. Anticytoplasmic (ACA) are found to be linked with some ANA negative (by IIF) samples, emphasizing the need for careful observation for ACA especially where ANA is not found. Conclusions: In most subjects, specific ENA targets correlated well with ANA-IIF patterns, implying effective cost minimization in CTD management. Similar future prospective studies (with clinical data) can provide a database and reference for our population.